Sandwich Plate System (SPS) with Polyurethane Elastomer for Submerged Floating Tunnel (SFT) - Hernadi, Ahmad; Suswanto, Budi (IPTEK Journal of Proceedings Series, 2017)
Submerged Floating Tunnel (SFT) i.e. Archimedes Bridge (AB) is a tubular structure that floats at a certain depth below the surface of the water carrying capacity exploiting derived from Archimedes lift. Various studies have been conducted on SFT but but no SFT has been constructed yet. The most important for design and build for SFT is the section. Research for the tube section of SFT has been doing for oval and circle shape with steel and concrete for the material, the conclusion is the section of the steel material with a circle is better than the cross section of the concrete. The section of SFT, which is identical to the vessel so that it is suitable when applied methods used on ships. One method that was developed in the vessel is Sandwich Plate System (SPS). SPS is a lightweight material that consists of two steel plates separated by a core in the form of elastomer. Elastomers which began much studied at the SPS is polyurethane. SPS advantage with polyurethane as the core has many advantages such as resistance to chemical reactions seawater, vibration and noise as well as strong against explosions.The tube shape is circle where inside diameter is 5 m, length is 150 m. Wave height is 5 m and wave period is 1.2 s with seabed -20m. Wave load will be applied to the tube as hydrostatic wave load arround the tube and dynamic wave load to the one side. Anlysis using Abaqus 6.14 and obtain the maximum and minimum stresses in x, y and z direction occure to the hole of cable in the belt and yied at the point. Maximum deflection in z direction is 83.466 mm in the same direction of load and y direction is 9.83 mm to the up side. Increament the step time makes the displacement is increase too.